Reduced reproductive capacity in Moina micrura Kurz, 1875 exposed to toxic Microcystis spp. - Shakri, Adibah; Md. Yusoff, Fatimah; Ismail, Intan Safinar; Toda, Tatsuki (Asian Fisheries Society, 2020)
Toxic cyanobacterial blooms are considered harmful to all consuming organisms along the aquatic food chain and top consumers, including humans. Hence this study was conducted to assess the impacts of two toxic Microcystis spp. on a tropical cladoceran, Moina micrura Kurz, 1875. Population growth studies and chronic bioassays were conducted using Microcystis aeruginosa (Kützing) Kützing, 1846, Microcystis viridis f. viridis (A. Braun) Elenkin, 1938, and a green alga, Chlorella vulgaris f. tertia Fott et Novakova, 1972 (as the control). Both Microcystis spp. negatively affected M. micrura. The population growth rate of M. micrura fed with C. vulgaris was 0.51 day-1 , while growth rates were negative when fed with M. aeruginosa (- 0.33 day-1 ) and M. viridis (- 0.13 day-1 ). In the chronic bioassay, the exposure of M. micrura to M. aeruginosa resulted in delayed production of M. micrura’s first batch of offsprings, which only occurred on day 6 compared to M. micrura fed with C. vulgaris which produced their first batch of offsprings earlier on day 3. This study showed that exposure of M. micrura to both toxic Microcystis spp. reduced the population density, fecundity, total offspring production and longevity of M. micrura compared to those fed with C. vulgaris.